Análise de acessibilidade e mobilidade para cadeirantes: estudo de caso nas calçadas da Avenida Brasil na cidade de Ilha Solteira - SP - Ostroski, Riane [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Accessibility is having the capacity and possibility of free access to spaces and services autonomously. When an individual is prevented from moving easily in a certain region due to physical obstructions, it not only denotes the existence of segregation in that particular environment, but also violates both Law 10,098, of December 19, 2000, which guarantees accessibility to all Brazilians, and the universal right to come and go. From the obtaining of a database related to the sidewalks of an avenue in Ilha Solteira, a municipality located in the state of São Paulo, this work carried out an analysis of this information, focusing, in particular, on the traffic conditions of wheelchair users. A bibliographic review was carried out in accordance with the topic to be addressed, as well as training in the use of the necessary Software and Hardware and, then, respectively, the delimitation of the region to be analyzed, the diagnosis and classification of the current situation according to the NBR 9050 (ABNT, 2020). It was concluded that the analyzed sidewalks are not accessible to wheelchair users because they have a large number of holes, irregularities, vegetation interference, among others. Most of the problems encountered were irregular pavement.

Acessibilidade é ter a capacidade e a possibilidade de acesso livre a espaços e serviços de forma autônoma. Quando um indivíduo é impedido de transitar com facilidade em determinada região devido a obstruções físicas, não só denota-se a existência de uma segregação nesse meio em particular, como também infringe-se tanto a Lei 10.098, de 19 de dezembro de 2000 que garante a acessibilidade a todos os brasileiros, quanto o direito universal de ir e vir. A partir da obtenção de uma base de dados relativos às calçadas de uma avenida em Ilha Solteira, um município situado no estado de São Paulo, esse trabalho realizou uma análise dessas informações, voltando-se, em especial, às condições de tráfego dos usuários de cadeira de rodas. Foi feita uma revisão bibliográfica condizente com o tema a ser tratado bem como o treinamento do uso dos Softwares e Hardwares necessários e, então, respectivamente, a delimitação da região a ser analisada, o diagnóstico e a classificação da situação atual segundo a NBR 9050 (ABNT, 2020). Concluiu-se que as calçadas analisadas não são acessíveis aos cadeirantes pois possuem grande quantidade de buracos, irregularidades, interferências de vegetação, entre outros. A maioria dos problemas encontrados foi a de pavimento irregular.
Analysis of accessibility and mobility for wheelchairs users: case study on the sidewalks of Avenida Brasil in the city of Ilha Solteira - SP
Keywords: Accessibility; Mobility; Sidewalks; Wheelchair; Acessibilidade; Mobilidade; Calçadas; Cadeira de rodas